2008
DOI: 10.1159/000121281
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids and Postprandial Glucose and Insulin Levels in Hyperlipidemic Subjects after Consumption of an Oat β-Glucan-Containing Ready Meal

Abstract: Background/Aims: To investigate whether a daily intake of a nutrient-balanced ready meal containing 4 g of oat β-glucans lowers total cholesterol (T-C) and low-density-lipoprotein cholesterol (LDL-C) in hyperlipidemic subjects and to evaluate its effect on postprandial glucose and insulin concentrations. Methods: A parallel, placebo-controlled trial was carried out in 43 healthy men and women with elevated serum cholesterol levels. During the 3-week run-in period, all subjects consumed daily a ready-meal soup,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…As discussed above, purified forms of β-glucan were found to be less successful at inducing changes in blood lipids 56 , 86 , 98 , 99 , 101 than intact oat tissues. 23 , 152 This is consistent with epidemiology studies showing that whole grain intake, but not fibre alone, is inversely associated with atherosclerotic progression and cardiovascular disease.…”
Section: Degree Of Processing and Functionalitymentioning
confidence: 92%
“…As discussed above, purified forms of β-glucan were found to be less successful at inducing changes in blood lipids 56 , 86 , 98 , 99 , 101 than intact oat tissues. 23 , 152 This is consistent with epidemiology studies showing that whole grain intake, but not fibre alone, is inversely associated with atherosclerotic progression and cardiovascular disease.…”
Section: Degree Of Processing and Functionalitymentioning
confidence: 92%
“…N, number of participants in each treatment group. Kestin et al, 1990Anderson et al,1991Stewart et al, 1992Uusitupa et al, 1992Johnston et al, 1998Berg et al, 2003Maki et al, 2003Biorklund et al, 2005Biorklund et al, 2008Karmally et al, 2005 Theuwissen LDL-cholesterol levels. In total, twenty-five studies investigating the cholesterol-lowering effect of oats were included in a subgroup analysis, and the authors reported a significant overall LDL-cholesterol reduction of −0•037 mmol/l (95 % CI − 0•047, −0•017) per g of oat fibre.…”
Section: Unclassifiedmentioning
confidence: 99%
“…Similarly, the consumption of 6 g/day of concentrated oat β -glucan in the form of powder for 6 weeks significantly reduced both total and LDL cholesterol in hypercholesterolemic adults, with the reduction in LDL cholesterol being greater than that in the control group [156]. A once-daily consumption of 4 g of β -glucans from oats, incorporated into a ready-meal soup, reduced LDL cholesterol levels by 3.7% over 5 weeks in a group of hyperlipidemic healthy subjects as compared with a control diet [157]. In contrast, in some studies, the reductions were small and nonsignificant, around less than 5% for LDL cholesterol, in comparison to control groups [158–162].…”
Section: Beta Glucan Obesity and Metabolic Syndromementioning
confidence: 99%